Caring for your baby and young child : birth to age 5 - Altmann, Tanya Remer; Hill, David L.; Middlemist, Martha C. (Bantam Books, 2024)
"You want to provide the best possible care for your child. And when you have questions, the 67,000 member pediatricians of the American Academy of Pediatrics (AAP) have answers. Based on the latest AAP recommendations, this evidence-based guide covers everything from preparing for childbirth to breastfeeding and from toilet training to starting school. The revised and updated eighth edition reflects current AAP policy statements and guidelines. Also included is a complete health encyclopedia addressing injuries, illnesses, congenital diseases, and other disabilities. New parents will find this pediatrician-approved guidance to be a lifesaver during middle-of-the-night health crises and when deciding whether to head to the pediatrician’s office, urgent care, or the emergency department."--Publisher.